Does the gut microbiome partially mediate the impact of air pollutants exposure on liver function? Evidence based on schizophrenia patients. (15th December 2021) - Yi, Weizhuo; Ji, Yifu; Gao, Hua; Pan, Rubing; Wei, Qiannan; Cheng, Jian; Song, Jian; He, Yangyang; Tang, Chao; Liu, Xiangguo; Song, Shasha; Su, Hong
Abstract: Air pollution may alter the composition of gut microbiome and subsequent liver-related metabolic disorders. Schizophrenia was often accompanied by liver dysfunction. But it was still unclear whether air pollutants affected liver function in patients with schizophrenia through gut microbiome. We aimed to clarify the impacts of long-term air pollutants on the gut microbiome and liver function in schizophrenia and to evaluate the intermediary effect of microbiome. Schizophrenia patients were recruited then serum biochemical indicators were tested. Air pollutant exposure in the previous year was retrospectively estimated by inverse distance weighting. The associations among air pollutants, gut microbiome, and liver function indicators in schizophrenia were estimated. Then the mediating effect of gut microbiome was further explored. The results showed that nitrogen dioxide (NO2 ), carbonic oxide (CO), ozone (O3 ), particulate matter with aerodynamic diameter ≤10 μm (PM10 ), and fine particulate matter (PM2.5 ) explained 2.68%–10.77% of the variation in gut microbiome composition (order level) in schizophrenia (all P  < 0.05). Network correlation analysis indicated that air pollutants and liver function indicators were mainly related to Firmicutes, Actinobacteria, and Proteobacteria in schizophrenia. Long-term NO2 exposure significantly increased the levels of gamma-glutamyl transpeptidase (GGT) and glutamic pyruvic transaminase (GPT) in schizophrenia. Coriobacteriales mediated 13.98% and 49.56% (all P  < 0.05) of the associations of long-term NO2 with GGT and GPT, respectively. To conclude, long-term NO2 exposure is positively associated with liver dysfunction in schizophrenia, in which gut microbiome plays an intermediary role. The two pathways, "NO2 -Coriobacteriales-GGT" and "NO2 -Coriobacteriales-GPT", would provide scientific evidence for the intervention of schizophrenia with liver dysfunction. Graphical abstract: Image 1 Highlights: Air pollutants were associated with the gut microbiome variation in schizophrenia. Coriobacteriales played an intermediary role in " NO2-liver function" pathways. "NO2-Coriobacteriales-GGT" and "NO2-Coriobacteriales-GPT" pathways were suggested. Coriobacteriales had diagnostic value in schizophrenia with liver dysfunction.